Atypical Polypoid Adenomyoma of the Uterus: An Immunohistochemical and Molecular Study of 21 Cases. (August 2015) - Němejcová, Kristýna; Kenny, Sarah L.; Laco, Jan; Škapa, Petr; Staněk, Libor; Zikán, Michal; Kleiblová, Petra; McCluggage, W. Glenn; Dundr, Pavel
Abstract : Atypical polypoid adenomyoma (APA) is an uncommon uterine lesion that commonly recurs after local excision and is occasionally associated with or precedes the development of atypical hyperplasia or endometrioid adenocarcinoma. Despite the fact that about 230 cases have been reported in the literature, only 2 studies of 6 and of 7 cases have investigated the molecular aspects; as such, molecular alterations that occur in APA remain largely unknown. We undertook a comprehensive immunohistochemical and molecular analysis of 21 cases of APA in 17 patients (including 4 recurrent/persistent lesions). The analyzed genes were PTEN and TP53 (by fluorescence in situ hybridization) and KRAS, BRAF, EGFR, and NRAS (all by polymerase chain reaction). Immunohistochemical staining was performed for PTEN, p53, mTOR, β-catenin, HNF-1β, and GLUT1 and for the mismatch-repair proteins MLH-1, MSH-2, MSH-6, and PMS-2. In most cases, there was nuclear expression of β-catenin in squamous morules and expression of HNF-1β, mTOR, and GLUT1 in the glandular component. All cases exhibited "wild-type" expression of p53. A common finding was loss of PTEN expression (6/19 cases). In 1 of these cases, loss of PTEN expression was accompanied by PTEN deletion. Mutation of the KRAS gene was found in 5/19 cases. Intact mismatch-repair protein expression was present in all cases, and TP53 abnormalities or mutations of EGFR, NRAS, or BRAF genes were not found. Given the association with atypical hyperplasia and endometrioid adenocarcinoma and the shared immunohistochemical and molecular features, we feel that, conceptually, APA is best regarded as analogous to a localized form of atypical hyperplasia.